Pedagogical accompaniment, research and analysis on the impact of extracurricular English class in a public school in Córdoba, Colombia (2021)
In this document, it will be possible to show an investigative project focused on teaching English to the youth of the municipality of Planeta Rica Córdoba, who will benefit from free English classes that will be taught by our professional pedagogues. On the other hand, in this paper, it would be possible to show the shortcomings that exist within the educational system in the area of English at the regional and departmental level in Colombia. This will be demonstrated in different results that young people from the department of Córdoba have obtained in the ICFES (Colombian Institute for the Education Evaluation) made in the region, which are below the standards of the National Ministry of Education (Ministerio de Educación Nacional). The investigators believe that the extracurricular classes are necessary for the students of this region. This is derived from the hypothesis that these classes will impact their English and, therefore, will help students improve their second language. We strongly think that these projects benefit the community, like the community this project is focusing on. The main function of the researchers within this project is making the administrative processes and that in this way the development of the classes is planned, organized, directed and implemented successfully by the teachers who will be in charge of the pedagogical part of the process. In this way is expected to achieve the objectives mainly proposed. Also, to carry out all this process it is necessary that there is organization and that everything is fully accomplished step by step and this requires being decisive to be able to achieve success. The research enabled a space where the young participants were benefited from one month of free English classes. This way, not only they, but the institution also has a participation in this benefit.